INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Bahronova Maftuna Farhodovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This paper explores the role of innovative technologies in the field of foreign language teaching. It focuses on how digital tools and advanced educational technologies  have  transformed  the  language  learning  process,  enhanced  student engagement, and provided opportunities for more personalized and effective language acquisition.